PENGARUH KECUKUPAN MODAL, KUALITAS ASET, RISIKO KREDIT, LOAN TO DEPOSIT RATIO, DAN SIZE TERHADAP KINERJA KEUANGAN BANK PERKREDITAN RAKYAT (Studi Kasus BPR Konvensional Pemerintah Daerah Di Jawa Tengah Periode 2012-2014) - Dewi Widyaningsih, 1342020046 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the factors affecting financial performance Conventional Rural Banks Local Government in Central Java. The sampling technique used in this research is purposive sampling. Data obtained a total population of 46 companies with a total of 138 samples of Conventional Rural Banks Local Government in Central Java, published by BI. The analysis technique used is multiple regression with the least square equation and hypothesis testing using t-statistic to test the partial regression coefficient and f-statistic to examine the effect together with the level of significance of 5%. The analysis showed that the variables of capital adequacy and Size a significant negative effect on the financial performance of BPR. Asset quality and loan to deposit ratio has a positive correlation, but not significant to the financial performance of BPR. Credit risk has no significant negative correlation to financial performance BPR. Keywords: capital adequacy, asset quality, credit risk, loan to deposit ratio, Size and financial performance